2022
DOI: 10.2147/prbm.s381092
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Empowering Leadership on Employee Improvisation: Roles of Challenge-Hindrance Stress and Psychological Availability

Abstract: The purpose of this research is to explore the effect of empowering leadership on employee improvisation, including the mediating roles of challenge stress and hindrance stress as well as the moderating role of psychological availability. Methods: Four proposed hypotheses were tested using hierarchical regression analysis and the bootstrapping method by reference to two waves of data collected in 2021 from 248 employees working for organizations located in southern China. Results:The results showed that empowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
(116 reference statements)
1
3
0
Order By: Relevance
“…In conditions characterized by JI, heightened PA bolsters employees’ confidence in the effectiveness of their voice, subsequently enhancing their inclination to participate in vocal behaviors aimed at exerting influence and driving change. This aligns with the results of Ren et al. (2022), where PA amplified the positive influence of challenge tension on employee improvisation and mitigated the adverse effects of hindrance stressors on employee improvisation.…”
Section: Discussionsupporting
confidence: 82%
“…In conditions characterized by JI, heightened PA bolsters employees’ confidence in the effectiveness of their voice, subsequently enhancing their inclination to participate in vocal behaviors aimed at exerting influence and driving change. This aligns with the results of Ren et al. (2022), where PA amplified the positive influence of challenge tension on employee improvisation and mitigated the adverse effects of hindrance stressors on employee improvisation.…”
Section: Discussionsupporting
confidence: 82%
“…It also showed that psychological capital and psychological empowerment are effective in reducing the levels of job burnout for teachers (Caglar & Yahya, 2018), and it has also found a significant effect of psychological capital on job creation, its dimensions, and job correlation among workers (Amin, 2019). Similarly, a study by Ren et al (2022) indicated that empowering leadership have a positive influence on employee improvisation, that mediated by challenge and hindrance stress. This refers to that empowering leadership advanced challenge stress and decreased hindrance stress of workers, thereby stimulating employee improvisation.…”
Section: Commenting On Previous Studiesmentioning
confidence: 97%
“…High levels of role stress have some potential for employee mood fluctuations and changes in behavior patterns, thereby triggering unethical behavior. Furthermore, some studies have identified stress as a possible consequence of empowering leadership [34]. Therefore, by drawing on existing research, this study will explore the mediating mechanisms of role stress to explain the mechanism influencing empowering leadership and UPB.…”
Section: Role Ambiguitymentioning
confidence: 99%